Accuracy of Intensity and Inclinometer Output of Three Activity Monitors for Identification of Sedentary Behavior and Light-Intensity Activity - Lucas J. Carr; Matthew T. Mahar (Hindawi Limited, 2012)
Purpose. To examine the accuracy of intensity and inclinometer output of three physical activity monitors during various sedentary and light-intensity activities. Methods. Thirty-six participants wore three physical activity monitors (ActiGraph GT1M, ActiGraph GT3X+, and StepWatch) while completing sedentary (lying, sitting watching television, sitting using computer, and standing still) light (walking 1.0 mph, pedaling 7.0 mph, pedaling 15.0 mph) intensity activities under controlled settings. Accuracy for correctly categorizing intensity was assessed for each monitor and threshold. Accuracy of the GT3X+ inclinometer function (GT3X+Incl) for correctly identifying anatomical position was also assessed. Percentage agreement between direct observation and the monitor recorded time spent in sedentary behavior and light intensity was examined. Results. All monitors using all thresholds accurately identified over 80% of sedentary behaviors and 60% of light-intensity walking time based on intensity output. The StepWatch was the most accurate in detecting pedaling time but unable to detect pedal workload. The GT3X+Incl accurately identified anatomical position during 70% of all activities but demonstrated limitations in discriminating between activities of differing intensity. Conclusions. Our findings suggest that all three monitors accurately measure most sedentary and light-intensity activities although choice of monitors should be based on study-specific needs.